Pathobiology of Aspergillus Fumigatus Endophthalmitis in Immunocompetent and Immunocompromised Mice - Gupta, Neha (Microorganisms, 2019)
Despite Aspergillus being the leading cause of exogenous fungal endophthalmitis following traumatic injury to the eye, its pathogenesis is not fully understood. In the current study, we developed a murine model of Aspergillus fumigatus (AF) endophthalmitis and investigated the disease pathobiology. Endophthalmitis was induced by intravitreal injection of Aspergillus spores in immunocompetent and immunocompromised (neutropenic) C57BL/6 mice, and disease severity was assessed by eye exam, fungal burden estimation, and histological examination. Our data showed that AF infection caused a time-dependent increase in corneal haze, opacity, and hypopyon beginning at two days post-infection (DPI). The fungal burden in infected eyes of immunocompetent mice peaked at 2 DPI and declined over 9 DPI. AF-infected neuroretina exhibited induction of innate immune response via upregulation of Toll-like receptors (TLRs) and inflammatory mediators (TNFα, IL-1β, and IL6), and increased polymorphonuclear neutrophil (PMN) infiltration. Histological analysis revealed heavy cellular infiltrates in the vitreous cavity as well as disruption of normal retinal architecture and increased retinal cell death. Neutropenic mice exhibited severe disease pathology with the prolonged fungal burden and increased inflammatory mediators. Our study described the first immunocompetent murine model of exogenous AF endophthalmitis and demonstrated an important role of neutrophils in innate defense against fungal endophthalmitis.